DNA barcoding confirms species rank for a cryptic geometrid species from Turkey and Bulgaria (Lepidoptera: Geometridae: Sterrhinae) - Can, Feza (Zootaxa, 2009)
Scopula drenowskii Sterneck, 1941, stat. n. is raised from the synonymy of Scopula decorata to species rank, based on differences in the male genitalia correlated to a considerable genetical distance in the DNA barcode region (COI). The ‘new’ species is known so far from Bulgaria and Turkey.